MELACAK ARGUMENTASI PENGGUNAAN SEMIOTIKA DALAM MEMAHAMI HADIS NABI - Afwadzi, Benny (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
ne"> During this time, the study of semiotics of hadith looks has less ofinteresting in the study of discourse text. Most scholars who engagedin this study prefer to bring semiotics to read the signs mentioned inverses of the Koran. In fact, the hadith of the Prophet himself as secondafter Koran contains the actual signs also interesting to uncover by thesemiotics. Through this paper, the author founds there are at least threearguments of using of semiotics in the understanding of the hadith,the fist, ‘semiotics’ turned out to have been used by classical scholars inunderstanding the hadith; second, the hadith is the language and thelanguage is a sign; and third, as a development of the hadith study inthe present era